IMPLEMENTASI MANAJEMEN INOVASI DALAM PENYUSUNAN MODUL AJAR PEMBELAJARAN - Rismawati, Desta (Jurnal Al-Hikmah, 2024)
This study aims to explore the development of teaching modules in the context of the Merdeka Curriculum, emphasizing qualitative research methods that focus on meaning, as highlighted by Sugiyono (2018). The research begins with formulating research questions that guide data collection and analysis. This field research uses a descriptive qualitative approach to gather primary data through interviews with a teacher at SMA 16 Bandar Lampung and classroom observations of 10th-grade students. The findings indicate that effective teaching strategies are crucial for delivering educational content in a specific learning environment (Gerlach & Ely, 2011). Constructing teaching modules is essential for teachers to design learning scenarios aligned with subject characteristics, student needs, and predetermined learning objectives. The study reveals that teachers can innovate teaching modules for Islamic Education subjects under the implementation of the Merdeka Curriculum. Key components include clear learning objectives, meaningful understanding through real-life connections, and engaging activities that stimulate student interest. Overall, the research underscores the importance of well-planned teaching modules in facilitating effective learning and assessment processes.